Mechanically durable and damage resilient dielectric elastomer actuators - Tan, Matthew Wei Ming (Nanyang Technological University, 2023)
Robots have become ubiquitous and integral to the daily lives of people. These robots are often composed of rigid structural materials that enable them to apply large loads and perform tasks with precision. However, these rigid robots lack compliance and adaptability, making them unsafe for human interactions and operating under unpredictable conditions. This has led to the emergence of soft robots that are composed of materials with similar moduli as biological materials. As such, soft robots demonstrate embodied intelligence principles at which their compliance allows them to adapt to various shapes. Soft actuators are a major component of these robots, being responsible for generating mechanical motion. While various soft actuators have been designed, dielectric elastomer actuators (DEAs) have become prominent due to their rapid response times, large actuation strains, and energy densities. However, electric fields to drive actuation require kilovolt range inputs that pose a safety concern and limits their compatibility with portable power sources. Owing to their soft nature, these DEAs are also susceptible to premature failure generated by physical damages within dynamic environments.